Lietuvių ir anglų kalbų holistinių veiksmažodžių semantinė erdvė - Špokienė, Vitalija (Kalbotyra, 1999)
The article presents a comparison of Lithuanian and English holistic verbs and investigates their equivalents at three levels of analysis; lexical, grammatical/syntactic and semantic. The comparative analysis shows that semantic classes of holistic verbs in both languages differ by the extent of coverage. The examination of lexical, grammatical and syntactic differences has implications for language teaching, translation practice and bilingual lexicography.